Contingent Valuation of Lake Rawapening as a Source of Drinking Water - Evi Irawan (Jurnal Ilmu Lingkungan, 2019)
The aim of this study is to estimate willingness to pay (WTP) of water consumers, by applying the contingent valuation method as a surcharge on their water bill, for a given improvement of the ecosystem of Lake Rawapening for ensuring the sustainability of freshwater supply in term quantity and quality as demanded by public water utility. The survey was conducted in Semarang regency involving 116 respondents in three villages that received clean water services from Lake Rawapening. The mean of WTP was estimated to be 6,055.54 rupiahs (0.433 US$) per month for each household, approximately equivalent to 9.26% of the average monthly water bill of households. The results revealed that younger educated respondents, households with higher income and with fewer members were, on average, were willing to pay more. This study also demonstrated that households’ ownership of shallow water wells was a hindering factor for contributing to improving lake’s ecosystem. The results of this study can assist decision‐makers to understand the public demand for improved the ecosystem of Lake Rawapening and to formulate better environmental policies.